2008
DOI: 10.1038/oby.2007.14
|View full text |Cite
|
Sign up to set email alerts
|

Could the Quality of Dietary Fat, and Not Just Its Quantity, Be Related to Risk of Obesity?

Abstract: This review focuses on the possible association between types of fatty acids and weight change. It examines the biological plausibility underlining these associations and the evidence obtained to date from clinical trials and epidemiological studies. Animal studies have shown that dietary short-and medium-chain fatty acids compared to long-chain fatty acids appear to promote weight loss. Similarly, monounsaturated fatty acids (MUFAs) appear to favor weight loss compared to saturated fatty acids (SFAs) in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 103 publications
(148 reference statements)
5
91
0
8
Order By: Relevance
“…Further, the HOP group had higher late postprandial fat oxidation at the initial test session than the CVP group. Differential oxidation of fatty acids varying in saturation have been reported (1,28) with higher rates noted for monounsaturated fatty acids (28). Consistent with this, the present trial noted that fat oxidation was augmented by consumption of high oleic acid peanuts compared to the conventional variety.…”
Section: Obesitysupporting
confidence: 79%
“…Further, the HOP group had higher late postprandial fat oxidation at the initial test session than the CVP group. Differential oxidation of fatty acids varying in saturation have been reported (1,28) with higher rates noted for monounsaturated fatty acids (28). Consistent with this, the present trial noted that fat oxidation was augmented by consumption of high oleic acid peanuts compared to the conventional variety.…”
Section: Obesitysupporting
confidence: 79%
“…Furthermore, unsaturated FAs have higher oxidation rates than does long-chain SFAs and the length of the carbon chain of SFAs is inversely correlated with the oxidation rate (Moussavi et al, 2008;McDonald et al, 1980). Indeed, b-oxidation is higher with an increase in polyunsaturated/saturated ratio intake and this ratio affects the utilization of FAs in the diet (Moussavi et al, 2008).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 99%
“…It was demonstrated that polyunsaturated fatty acids (PUFA), but not monounsaturated fatty acids (MUFA) or saturated fatty acid (SFA) suppress the expression of genes involved in lipogenic transcription and are better activators of PPAR-a,g (Moussavi et al, 2008). Furthermore, unsaturated FAs have higher oxidation rates than does long-chain SFAs and the length of the carbon chain of SFAs is inversely correlated with the oxidation rate (Moussavi et al, 2008;McDonald et al, 1980). Indeed, b-oxidation is higher with an increase in polyunsaturated/saturated ratio intake and this ratio affects the utilization of FAs in the diet (Moussavi et al, 2008).…”
Section: Circulating Free Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent review suggested that it may be not so much the amount of fat as the type of fat that should be considered. 10 Trans fatty acids (TFAs) are monounsaturated fatty acids (MUFAs) or polyunsaturated fatty acids (PUFAs) that contain at least one double bond in the trans configuration, rather than the usual cis configuration found in most lipids. This configuration may occur either as a result of microbial fermentation in the rumen (leading to the presence of TFA in dairy products or the meat of ruminants) or through the process of hydrogenation (giving rise to TFAs in spreadable fats that are commonly used in the baking industry).…”
Section: Introductionmentioning
confidence: 99%